THE IMPACT OF THE USE OF PROFICIENCY-BASED RUBRICS ON STUDENT GRADING - Cayton, Chena Williams (East Carolina University, 2015)
The purpose of this study is to determine impact of the proficiency-based rubric on student learning, the teacher’s ability to provide consistency in student grading, and communication to parents regarding the child’s academic achievement in kindergarten, first and second grade in one Local Education Agency (LEA) in eastern North Carolina. Based on literature review, proficiency-based rubrics are an effective tool for teachers to use to help promote clarity and consistency in grading. Marzano (2000), Brookhart (2009), Guskey and Bailey (2001), and O’Connor (2002) are just a few of the researchers that provided examples of how rubrics assist teachers in effectively measuring student achievement. Therefore, this research study examined whether proficiency-based rubrics were effective in: (1) producing consistency in grading, (2) equipping teachers with a tool to convey to parents their child’s proficiency and (3) producing a positive impact on student achievement. The data used for this research study were collected from one LEA in eastern North Carolina. Teacher and principal perception as to the impact of the use of the proficiency-based rubric was collected through survey and focus group interviews. To answer the research questions, data were analyzed from surveys and focus group interviews given to both principals and teachers within the Pitt County School District. In order to provide findings regarding the research questions, survey and interview questions were categorized under the classifications of impact, consistency or communication. The data from the surveys and focus group interviews were triangulated in order to effectively summarize the data that were collected. The data from K-2 principals and teachers revealed that both participant groups perceived the proficiency-based rubrics had a positive impact on student grading. However, the data revealed a higher percentage of principals believed the use of the rubrics a more positive effect on student grading as compared to teachers’ beliefs. Based on the findings, consistent grading policies and procedures need to be established by the district as well as continuous professional development for principals and teachers. Additionally, teacher and principal preparation programs need to ensure pre-service candidates are exposed to, and know the value of proficiency-based rubrics on student learning.
Keywords: Grading; Rubrics; Proficiency; Consistency; Grading and marking (Students)--North Carolina; School children--North Carolina; Academic achievement--North Carolina